2003
DOI: 10.1007/s00421-003-0833-3
|View full text |Cite
|
Sign up to set email alerts
|

Muscle hypertrophy, hormonal adaptations and strength development during strength training in strength-trained and untrained men

Abstract: Hormonal and neuromuscular adaptations to strength training were studied in eight male strength athletes (SA) and eight non-strength athletes (NA). The experimental design comprised a 21-week strength-training period. Basal hormonal concentrations of serum total testosterone (T), free testosterone (FT) and cortisol (C) and maximal isometric strength, right leg 1 repetition maximum (RM) of the leg extensors were measured at weeks 0, 7, 14 and 21. Muscle cross-sectional area (CSA) of the quadriceps femoris was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
234
3
36

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 357 publications
(329 citation statements)
references
References 36 publications
39
234
3
36
Order By: Relevance
“…In the present study, KAATSU-walk training produced a hypertrophic potential of 0.14% per session (~2% increase in muscle volume over 18 training sessions), which is similar to that observed following high-intensity resistance exercise training (Ahtiainen et al, 2003;Jones and Rutherford, 1987). The similarity in hypertrophic potential highlights the importance of the compressed training duration employed during KAATSU-walk training with very low exercise intensities.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the present study, KAATSU-walk training produced a hypertrophic potential of 0.14% per session (~2% increase in muscle volume over 18 training sessions), which is similar to that observed following high-intensity resistance exercise training (Ahtiainen et al, 2003;Jones and Rutherford, 1987). The similarity in hypertrophic potential highlights the importance of the compressed training duration employed during KAATSU-walk training with very low exercise intensities.…”
Section: Discussionsupporting
confidence: 83%
“…These authors observed that 3 weeks of twice-daily KAATSU-walk training produced significant muscle hypertrophy (4-7% increase in muscle volume) and increased dynamic and isometric strength (8-10% increase) in the thigh muscles despite the very low intensity of the exercise. The magnitude of muscle hypertrophy and strength gains as well as the hypertrophic potential (percent change in muscle volume divided by the number of Skeletal muscle size and strength are increased following walk training with restricted leg muscle blood flow: implications for training duration and frequency training sessions) is comparable with previous results following HIT (Ahtiainen et al, 2003;Jones and Rutherford, 1987), although greater training effects following HIT have been reported (Akima et al, 1999;Bell et al, 1992;Seynnes et al, 2007;Tesch et al, 2004).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Thus, a heightened anabolic environment seemingly enhances the ability for novice RT participants to achieve greater net protein accretion compared to trained individuals. In support of this hypothesis, Ahtiainen et al (Ahtiainen et al 2003) compared the quadriceps femoris crosssectional area following 21 weeks of heavy RT in untrained and trained subjects. After 21 weeks, only the untrained group demonstrated significant hypertrophy, while the trained group had reached a plateau in muscular adaptations.…”
Section: Discussionmentioning
confidence: 97%
“…For this reason, our protocol utilized large (back squat) and small (bench press and shoulder press) muscle groups. Variables that influence GH secretion include 1) the amount of muscle mass recruited, which directly affects the metabolic and hormonal responses to RE (3), and 2) the total work performed, which affects GH release (1). Still other variables include intensity, volume, rest interval between sets, and magnitude of total work done.…”
Section: Discussionmentioning
confidence: 99%